Biomechanical adaptation in ice hockey skating - Pearsall, D. J.; Turcotte, R. A.; Levangie, M. C.; Forget, S. (Routledge handbook of ergonomics in sport and exercise, 2016)
The defining trait of the sport of ice hockey is its environment of play and its manner of locomotion: ice and skating. Flat ice surfaces afford both unique physical obstacles and assets to locomotion. Its inherent lower contact friction than normal terrain excludes conventional human walking and running patterns since sufficient ground reaction force (GRF) cannot be generated at the interface of foot and ground to propel the body forward. However, ice surfaces between temperatures of 0 and - 10°C are remarkable (Bowden, 1955; de Koning et al., 1992). They can be etched with sufficient sharp tools, providing the potential for a foothold for push-off. Furthermore, when a sharp blade is moved rapidly across the surface, sufficient frictional energy may be generated to heat then momentarily melt the ice, creating a transient boundary lubrication between blade and ice: that is, the potential to glide. If a tool can be manipulated to alter between these high and low surface friction states, then adapted locomotion patterns are possible. This is the essence of skating: when the blade is oriented more or less perpendicular to the intended direction of motion, adequate GRF is possible for propulsion; when the blade is oriented parallel to the intended direction of motion, remarkably low friction impedance occurs during glide. Of course, ample time and training are required to readapt learned walking and running motor patterns to this more challenging surface; yet the rewards are amazing, exhilarating speeds of movement.